Alaska region overview : a legacy of caring for the land and serving people. - United States. Forest Service. ([Washington, D.C.?] : U.S. Dept. of Agriculture, 2001)
This look at the circumstances and amenities of Alaska emphasizes matters under Forest Service oversight. "R10-MR-13"--P. [2] of cover. "July 2001"--P. [2] of cover. Shipping list no.: 2001-0298-P. Cover title. This look at the circumstances and amenities of Alaska emphasizes matters under Forest Service oversight. Mode of access: Internet. 2